Assessment of Drug-Related Problems among Inpatients in a Tertiary Care Hospital of Eastern Nepal - Adhikari, Rashmi; Dahal, Prasanna; Khadka, Sitaram; Mallik, Shyam Kumar; Alam, Kadir (Journal of Karnali Academy of Health Sciences, 2021)
Background: Drug-related Problems are major safety concerns in hospitalized patients; failure to prevent those medications related errors may lead to therapeutic failure, adverse effects, and poor therapeutic outcomes. This study aims to assess drug-related problems in the medicine ward of a tertiary care hospital in Eastern Nepal. Methodology: Prospective observational study was conducted from March to August 2019. Descriptive analysis was performed, and Bivariate analysis using chi-square was used to test the association between demographic characteristics and drug-related problems. Results: 365 patients were selected, of which 96 patients had drug-related problems. A total of 127 drug-related problems were documented. The most common drug-related problems were drug and therapeutic duplication 31(24.4%), a drug prescribed but no clear indication 22(17.3%), potential ineffective therapy 16(12.6%), inappropriate duration 11(8.7%), and adverse drug reaction 10(7.8%). The majority of recommendations provided by the pharmacist were drug discontinuation 57(44.9%), followed by drug change 16(12.6%), and the need for antibiotic susceptibility testing 14(11%). Antimicrobials 75(59.1%) was the most frequent drug class involved in drug-related problems followed by Corticosteroids 12(9.4%), and non-steroidal anti-inflammatory drugs 8(6.3%). A significant association with drug-related problems occurrences was found between age groups, length of hospital stays, and polypharmacy which was significant at p<0.05 Conclusion: Nearly one-fourth of hospitalized inpatients had drug-related problems. Drug and therapeutic duplication were the most common drug-related problems followed by a drug prescribed without clear indication, potential ineffective therapy, and inappropriate duration. The pharmacist plays a crucial role in identifying and resolving drug-related problems during inpatients care.